UPAYA PERTAMINA HULU ROKAN DALAM MENDUKUNG PENCAPAIAN NET ZERO EMISSION 2060 - Rianto, Farel; Takwa, Tuah Kalti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study examines Pertamina Hulu Rokan's efforts in supporting the achievement of Indonesia's 2060 Net Zero Emission (NZE) target. The research background is based on the increasing greenhouse gas emissions caused by human activities. Leading to global climate change and significant environmental impacts. It considers both global and national contexts, including commitments to the Paris Agreement and Indonesia's NZE 2060 program. Using a qualitative approach, data was collected through literature studies, policy document analysis, and interviews with experts and relevant stakeholders. The theoretical framework integrates the Neo-liberal Institutional perspective and International Regime Theory, providing a foundation for understanding the interaction between international norms and national policies, the role of non-state actors, and the contribution of state-owned enterprises (SOEs) in the clean energy transition. NZE norms, previously limited to the international level, will influence national and corporate policies once ratified. Keywords: Pertamina Hulu Rokan, Net Zero Emission, International Regime